Contributions to the flora of Budapest and its surroundings III. - Somlyay, Lajos; Csábi, Miklós (Kitaibelia)
New or recently confirmed localities of 40 rare taxa (including 7 ferns) are presented from the vicinity of Budapest. Some records are new for the flora of particular regions, specifically: Geranium sibiricum (Buda Mts and Budapest), Polystichum setiferum (Pilis Mts), Onosma pseudarenaria, Sorbus aria s. str. (Visegrad Mts). Of the remaining records, the most significant ones are those of Agrimonia procera, Botrychium lunaria, Epipactis tallosii, Gymnadenia odoratissima and Sorbus ujhelyii. Cikkünk 40 ritka taxon (köztük 7 páfrány) új vagy megerősített adatait tartalmazza Budapest környékéről. Közülük egy faj (Geranium sibiricum) a Budai-hegység, ill. Budapest flórájára, egy (Polystichum setiferum) a Pilis flórájára, kettő (Onosma pseudarenaria, Sorbus aria s. str.) pedig a Visegrádi-hegység flórájára új. További adataink közül kiemeljük az Agrimonia procera, Botrychium lunaria, Epipactis tallosii, Gymnadenia odoratissima és Sorbus ujhelyii új előfordulásait.